Assessment of frailty, performance and functional independence in patients with periprosthetic fractures associated with total hip arthroplasty - Victor Niculesc; Razvan Ene; Alexandru Lisias Dimitriu; Sebastian Tirla; Cristian Marge; Mircea Gheorghe Pop; Radu Dan Necula (Balneo and PRM Research Journal)
Periprosthetic fractures (PFs) associated with total hip arthroplasty are significant postoperative complications after hip prosthesis implantation surgery. The aim of this study was to evaluate the fragility, performance and functional independence of patients with PFs associated with total hip arthroplasty. A cross-sectional study was conducted between January and October 2024. The 101 patients evaluated were divided into 3 groups: the group consisting of hip arthroplasty patients - named ATS group (n=36), the group consisting of periprosthetic fractures patients - named PF group (n=11), the group consisting of stage III and IV coxarthrosis patients - named OAH group (n=42). Mean scores fall in the range of pre-fragility - mild frailty for ATS and OAH groups (7.098 ± 2.289 vs. 6.939 ± 1.405), with no significant differences between them, while the mean score of PF group falls in the range of moderate-severe frailty (11.727 ± 3.289). Our data analysis suggests a marked impairment of functional independence in more than 90% of PF patients versus 32% of patients in the ATS group and about 20% of patients in the OAH group; about 75% of patients in the PF group have a significant impairment of functional perfomance. Periprosthetic hip fractures are associated with advancing age and increased fragility. Functional performance and independence of patients with periprosthetic fractures, more than 3 months after fracture, is significantly impaired and is associated with frailty status and advanced age